Analisis Mitigasi Risiko Pembiayaan Bermasalah Pada PT BPRS Amanah Ummah KC Cicurug - Zannah, Mitha Miftahul; Dewi, Afiatin (Jurnal Iqtisaduna, 2025)
This study aims to analyze the risk mitigation carried out by BPRS Amanah Ummah KC Cicurug in minimizing non-performing financing and to determine financing products with high risk. The type of research used is a case study with a qualitative approach. Data collection techniques are interviews, observation, and documentation. The data analysis technique uses the Nvivo 12 pro analysis tool with the Miles and Huberman data analysis model, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that the mitigation of the risk of non-performing financing is done by applying the 1S + 5C principle, the financing rating model by classifying customer financing opportunities based on the rating level, financing portfolio management is carried out by tiered limitation, gradual disbursement, prohibition of certain party financing, and allowance for productive asset losses (PPAP), recovery management by looking for potential financing and conditioning the allocation of PPAP funds, financing diversification by not channeling financing to one business sector. High risk financing products are financing with mudharabah, musyarakah, musyarakah mutanaqisah (MMQ), Ijarah Muntahiyya Bit Tamlik (IMBT) and murabahah contracts.